Assessment of German-Pakistani relations in trade, investment and strategic cooperation - Talat Mahmood (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
German-Pakistani relations cannot be analyzed in isolation of the larger domestic and international trajectories, economic and political, on both sides of the partnership. After a recent democratic power transfer in 2013, Pakistan continues to face complex challenges. The instable security situation in the region exerts pressure on the Pakistani state, multiplying domestic challenges like macroeconomic and trade instability, societal conflicts and crises in energy supply and infrastructure. In light of these aspects, this paper explores the magnitude and development of German-Pakistani relations, focusing especially on trade, economic cooperation and strategic interests on both sides. The analysis of the German-Pakistani trade and investment relations over the last decade show only very moderate volumes with room for expansion. These dynamics are mirrored in private trade business relations with German SME's active on the Pakistani market (mostly through agents) and a lack of internationalization and economic diversification among Pakistan's private businesses. A related structural reason for these predicaments is the lack of a dedicated and clearly-defined policy infrastructure among both states, resembling the long-standing and amicable, though unenthusiastic German-Pakistani relationship. The recent EU-Waiver assignment, the adoption of the EU's GSP+ and related trade diversification programs signify the most significant parts of the EU-Pakistani partnership, and mirror an integral part of the discourse in German-Pakistani relations. Pakistan should attempt to reap the benefits of these developments. Strategic relationships between Germany and Pakistan need to be developed further and strengthened. The content of a recent bilateral signing of a multifaceted roadmap for strategic dialogue among Germany and Pakistan has to be implemented effectively.
Keywords: F13; F14; F21; F35; F59; H77; I38; L24; L25; N45; 300; Trade policy; Country and Industry Studies of Trade; International Investment; Foreign aid; International relations and political economy; Intergovernmental Relations; Govt. policy; Joint ventures; Diversification; Asia & Middle East